BULK SOLID STATE CoPOLYME RIZATION OF AcR YLA MIDE WITH PHTHA LIC ANHYDRIDE UV-IRRADIATION AT 60+1°C (Biological Sciences - PJSIR, 2001)
Bulk solid state copol ymerization of acrylamide (r 1 ) with phth alic anhydride (r2) under UV-irradiation was carried out at60°C a temperature below the m .p. of reactan ts . It was observed th at y ield of the products differed for different sets ofexperi ments but the trend remai ned same. The monomer reactivity ratios r 1 = 1 .4 and r2 = 0 were determi ned graphica ll y by  u sing the arranged form of copol ymer composi ti on equation. Molecular  weights of the products  were determi n ed   as3.0 x 105 - 5.5 x 1 OS. All copolymer samples were off w h i te i n colour whi ch became light yellow at l 40°C.